(untitled) (Swiss Medical Weekly, 2015)
QUESTIONS UNDER STUDY: Studies from several countries (Scandinavia, United Kingdom) report that general practitioners (GPs) experience problems in sickness certification. Our study explored views of Swiss GPs towards sickness certification, their practice and experience, professional skills and problematic interactions with patients. METHODS: We conducted an online survey among GPs throughout Switzerland, exploring behaviour of physicians, patients and employers with regard to sickness certification; GPs’ views about sickness certification; required competences for certifying sickness absence, and approaches to advance their competence. We piloted the questionnaire and disseminated it through the networks of the five Swiss academic institutes for primary care. RESULTS: We received 507 valid responses (response rate 50%). Only 43/507 GPs experienced sickness certification as problematic per se, yet 155/507 experienced problems in sickness certification at least once a week. The 507 GPs identified estimating a long-term prognosis about work capacity (64%), handling conflicts with patients (54%), and determining the reduction of work capacity (42%) as problematic. Over 75% would welcome special training opportunities, e.g., on sickness certifications during residency (93%), in insurance medicine (81%), and conflict management (80%). CONCLUSION: Sickness certification as such does not present a major problem to Swiss GPs, which contrasts with the experience in Scandinavian countries and in the UK. Swiss GPs did identify specific tasks of sickness certification as problematic. Training opportunities on sick-leave certification and insurance medicine in general were welcomed.